1972
DOI: 10.1172/jci106978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free fatty acids on myocardial function and metabolism in the ischemic dog heart

Abstract: A B S T R A C T Since elevation of plasma concentrations of free fatty acids (FFA) increases myocardial oxygen consumption without influencing mechanical performance in normal hearts, it was the purpose of this study to determine whether FFA would modify mechanical performance at limited oxygen supply. Left coronary blood flow was reduced by gradual clamping of a shunt from the left carotid artery until moderate ventricular dilatation supervened. Left ventricular systolic pressure (LVSP), its maximal rate of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(55 citation statements)
references
References 40 publications
3
51
1
Order By: Relevance
“…Under normal conditions, amino acids contribute little to acetyl-CoA, but, in post-ischemic myocardium, aspartate and glutamate may indirectly alter substrate selection by stimulating both pyruvate transamination and glycolysis (20). Any shift from fatty acids to carbohydrates would be beneficial because ofoxygen sparing, which has been documented in animal models (21)(22)(23) and supported by clinical observations (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 75%
“…Under normal conditions, amino acids contribute little to acetyl-CoA, but, in post-ischemic myocardium, aspartate and glutamate may indirectly alter substrate selection by stimulating both pyruvate transamination and glycolysis (20). Any shift from fatty acids to carbohydrates would be beneficial because ofoxygen sparing, which has been documented in animal models (21)(22)(23) and supported by clinical observations (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 75%
“…Since that time, many studies have assessed myocardial metabolism in vivo in animals and humans by measuring the chemical concentration of free fatty acids in the artery and coronary sinus (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The arterial-coronary sinus chemical differences suggested that free fatty acids (fatty acids bound to albumin) were the preferred myocardial substrate in the fasting, resting state.…”
Section: Introductionmentioning
confidence: 99%
“…After release, and return of the electrocardiogram to normal values, drug administration was initiated, and another epicardial map 2 100 ml contains: fractionated soya bean oil, 10 g; fractionated egg lecithin, 1.2 g; glycerol, 2.5 g; water added up to 100 ml. Main fatty acid components are linoleate (40%), oleate (24%), palmitate (10%), and linolenate (7%o) (12). of S-T segments was obtained.…”
mentioning
confidence: 99%
“…Marked depression of myocardial contractility has been observed in oxygen-limited hearts receiving high concentrations of FFA (11,12). This has been attributed to increased oxygen demand (12), suggesting that FFA in high concentrations contribute to the myocardial cell injury. Multiple epicardial electrocardiographic measurements were performed with a cotton wick electrode, as described previously (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation